Relationship between internationalization and corporate social responsibility performance: Evidence from Chinese listed companies / Su Yu - Su , Yu (2021)
Corporate Social Responsibility (CSR) has gained increasing attention as a tool for companies to maintain their reputation and competitive advantage. Previously, Chinese companies did not have a good reputation internationally due to issues such as product quality and human rights concerns. With the encouragement of the government through policies such as the “The Belt and Road Initiative”, Chinese companies began to focus their efforts on internationalization. This study investigates whether the internationalization of Chinese listed companies will affect their CSR performance. In addition, financial performance and state ownership are introduced to explore whether they moderate the relationship between internationalization and CSR performance. In this research, a total of 2030 observations from 406 listed companies in Shanghai and Shenzhen Stock Exchanges are studied from 2013 to 2017. In order to ensure the robustness of the results, this study used Pooled OLS model, Fixed effect model and Dynamic panel model to test the hypotheses. The results suggest that the internationalization of Chinese listed companies has a positive impact on CSR performance. Financial performance has a negative moderating effect on the relationship between internationalization and CSR, while the results suggest that state ownership does not have a moderating effect. The results of this study are consistent with the results from prior literature such as Attig et al. (2014) and Kang (2012). The results suggest that Chinese listed companies that are involved in internationalization are associated with better CSR performance. Due to the social and cultural differences between China and developed countries, the previous conclusions on CSR and internationalization in developed countries may not be applicable in the context of China. Accordingly, this study contributes to the limited literature on CSR and internalization in the context of Chinese listed companies whereby results from this study suggest that companies should not only focus on profits and ignore sustainable development. This study has several limitations. Firstly, the results may not be generalizable to other countries, because this study is based on China’s institutional environment. Secondly, the results of this study may not be generalizable to all Chinese companies, as it was only conducted on listed companies.